2021
DOI: 10.1215/00703370-9099310
|View full text |Cite
|
Sign up to set email alerts
|

DACA's Association With Birth Outcomes Among Mexican-Origin Mothers in the United States

Abstract: The 2012 Deferred Action for Childhood Arrivals (DACA) program granted work authorization and protection from deportation to more than 800,000 young undocumented immigrants who arrived to the United States as minors. We estimate the association between this expansion of legal rights and birth outcomes among 72,613 singleton births to high school–educated Mexican immigrant women in the United States from June 2010 to May 2014, using birth records data from the National Center for Health Statistics. Exploiting t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…Two studies of minimum-wage levels and one study of EITC expansion (36, 37, 40) found positive effects of increased minimum wage on health inequities, supporting unconditional cash transfers that can impact daily living. Similarly, two studies of DACA found reduced inequities (47,51), possibly because the opportunities granted by DACA affect many areas of life.…”
Section: Environmentalmentioning
confidence: 95%
See 3 more Smart Citations
“…Two studies of minimum-wage levels and one study of EITC expansion (36, 37, 40) found positive effects of increased minimum wage on health inequities, supporting unconditional cash transfers that can impact daily living. Similarly, two studies of DACA found reduced inequities (47,51), possibly because the opportunities granted by DACA affect many areas of life.…”
Section: Environmentalmentioning
confidence: 95%
“…Eight studies evaluated the effect of immigration-related policies on Hispanic/Latinx populations in the USA (Table 1). Six studies evaluated the effects of anti-immigration on health or other health outcomes (42,(48)(49)(50)58), and two studies evaluated the effect of the Deferred Action for Childhood Arrivals (DACA) policy (47,51). In alignment with the WHO CSDH framework (28), each of these policies affect governance and in uence one's socioeconomic position based on race and/or ethnicity (Fig.…”
Section: Immigrationmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, Kuka et al (2020) find that DACA significantly increased high school attendance and high school graduation rates. There is also increasing evidence that DACA improved mental health (Venkataramani et al, 2017;Giuntella and Lonsky, 2020;Hainmueller et al, 2017;Patler et al, 2019;Giuntella et al, 2021) and birth outcomes (Hamilton et al, 2021), reduced teenage fertility (Kuka et al, 2019), and crime (Gunadi, 2020).…”
Section: Background 21 Deferred Action For Childhood Arrivals (Daca)mentioning
confidence: 99%